Development bank lending in Nigeria : the Federal Loans Board - Schatz, Sayre P. (Ibadan : Published for the Nigerian Institute of Social and Economic Research [by] Osford University Press, 1964)
This book is about development banks which are designed to stimulate private economic activities
Bibliographical footnotes.
oo 23/01/2019
Loans
Keywords: Government lending